Identifying the Components of Preschool Curriculum Model based on Bronfenbrenner\'s Ecological Systems Theory - Mohammad Panahandehpour; Ahmad Hashemi; Mokhtar Ranjbar; Abbas Goltash (Iranian Journal of Educational Research)
Objective: This study aimed to identify the dimensions and components of the preschool curriculum based on Bronfenbrenner's Ecological Systems Theory. Methods: The study utilized both qualitative and quantitative methods to evaluate the dimensions and components of the preschool curriculum model. The researchers investigated articles, books, and research papers conducted both domestically and internationally on reputable and authenticated online database networks, spanning from 2000 to 2023. Descriptive and inferential statistical analyses were conducted using SPSS statistical software in the quantitative phase. The statistical population of the study was 371 principals of pre-schools located in Bushehr province in the academic year 2021-2022, and by using the Krejci-Morgan table, we selected 181 Principals as a sample.  To validate the quantitative section of the study, the confirmatory factor analysis was conducted. Results: The results of the study revealed that the preschool curriculum model had seven components,  including: paying attention to educating and informing families; utilizing new and creative teaching methods in preschool; paying attention to the role and effects of communication and an appropriate educational environment; comprehensiveness and appropriateness of the educational content of preschool programs; educational facilities and resources, appropriateness of the preschool programs with society’s culture; and the role of governance of macro-management in supporting preschool program. Conclusion: Based on the findings, we conclude that the integration of Bronfenbrenner's Ecological Systems Theory into the design of a preschool curriculum holds great potential for creating a more comprehensive and effective educational experience for young children.